2021
DOI: 10.3390/su13116457
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urban Greening Strategies for Environmental Sustainability—A Review and Assessment in the Context of Saudi Arabian Megacities

Abstract: The review and assessment of urban greening patterns play a crucial role in sustainable urban planning and green spaces (GSs) management, helping to improve human well-being. In recent years, various methods and strategies were applied to examine the relationship between GSs and environmental sustainability, but so far, no studies on systematic review and empirical assessments were carried out in Saudi Arabian context. Thus, a comprehensive review and assessment of current GSs patterns and planning strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 95 publications
(131 reference statements)
1
1
0
Order By: Relevance
“…In Jeddah, urban parks are not large areas, but they play a significant role in the well-being of urban citizens (e.g., providing physical and mental health benefits) due to otherwise insufficient opportunities for contact with nature. Thus, the urban gardens/parks in Jeddah are perceived as important for spending time in outdoor spaces (Addas and Maghrabi 2021b ) and have been highly recognized for their benefits or cultural services, with our findings similar to those of previous research (Swamy and Devy 2010 ; Paul and Nagendra 2017 ; Swapan et al 2017 ) (Table 8 ).…”
Section: Discussionsupporting
confidence: 88%
“…In Jeddah, urban parks are not large areas, but they play a significant role in the well-being of urban citizens (e.g., providing physical and mental health benefits) due to otherwise insufficient opportunities for contact with nature. Thus, the urban gardens/parks in Jeddah are perceived as important for spending time in outdoor spaces (Addas and Maghrabi 2021b ) and have been highly recognized for their benefits or cultural services, with our findings similar to those of previous research (Swamy and Devy 2010 ; Paul and Nagendra 2017 ; Swapan et al 2017 ) (Table 8 ).…”
Section: Discussionsupporting
confidence: 88%
“…Meeting the UN standard of 30 m 2 per capita would require substantial green space expansion in Jeddah. Furthermore, Addas [62] analyzed green space distribution across Saudi cities, discovering six primary urban-greening strategies backed by local evidence. The study found that Dammam had the largest per capita area at 5.4 m 2 , followed by Riyadh at 1.18 m 2 and Jeddah at 0.5 m 2 .…”
Section: Discussionmentioning
confidence: 99%